The Application of Mobile Technology in Educational Administration to Foster Continuous Learning and Professional Development - Qiao, Ying; Li, Yunfang; Li, Mintian (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study explores the application of mobile technology in educational administration to promote continuous learning and professional development. By conducting a quantitative analysis of the interaction level and activity consistency within mobile networks and proposing strategies based on mobile network knowledge sharing mechanisms, this research aims to enhance our understanding of how mobile technology operates in educational management. It also aims to offer theoretical support and practical guidance for educational management practices. Currently, the integration of mobile technology in educational management has become a prominent research topic. Existing studies, however, lack sufficient quantitative analysis regarding interaction levels and activity consistency within mobile networks. Moreover, research on mobile network knowledge-sharing mechanisms that foster continuous learning and professional development is relatively limited. Therefore, this study addresses these research gaps and offers new perspectives and methodologies for a deeper understanding of the application of mobile technology in educational management.